ANALISIS REGRESI LOGISTIK BINER UNTUK MEMPREDIKSI PROBABILITAS KELULUSAN MAHASISWA PADA MATA KULIAH MATEMATIKA FARMASI - Siti Fatimah Sihotang (Universitas Islam Sumatera Utara, 2023)
Almost all students certainly expect to get graduation and satisfactory results when Final Semester Examination results are announced. It is because Final Semester Examination is a measurement in order to map and see the ability of students after participating in the learning process within a certain period of time, by conducting tests through various tests. Apart from depending on each individual student, there are also several factors that affect graduation and obtaining good grades at Final Semester Examination, namely the number of study hours in a day and the acquisition of Mid Semester Examination score. Thus this study aims to find out how the influence of the number of study hours in a day and the results of the midterm exam has on the graduation of the final semester exam in pharmacy mathematics. The data analysis method used is the Binary Logistic Regression method. From the research, results it is known that the independent variables study hours in a day and the acquisition of Mid Semester Examination scores have a significant effect on graduation, which is equal to 59.5%.. In addition, it is also known that the more hours of study in a day and the higher the Mid Semester Examination score, the higher the chance of passing Final Semester Examination with satisfactory grades.